TI_GERICHTE 12.2016.141 vom 5. März 2018 , Appalto - rappresentanza del direttore dei lavori - rinuncia alla forma pattuita - TI Tribunale d'appello (2018)
Appalto - rappresentanza del direttore dei lavori - rinuncia alla forma pattuita